Induction coil gun - Matos, Vítor (2006)
This paper describes a device capable of throwing metal rings at a range of a few meters. Part of an iron pipe is inserted on a coil. A conducting non-ferromagnetic ring is inserted in the pipe through its other extremity. An alternating current flowing through the coil creates an alternating magnetic field, which magnetizes the iron pipe. So, an alternating magnetic field is created around the pipe and induces a circumferential current flowing in the ring. This current is repelled by the magnetic field, forcing the ring to jump out of the pipe.